Protective Effects of Red Ginseng Against Tacrine-Induced Hepatotoxicity: An Integrated Approach with Network Pharmacology and Experimental Validation - Kim BJ; Bak SB; Bae SJ; Jin HJ; Park SM; Kim YR; Jung DH; Song CH; Kim YW; Kim SC; Lee WY; Park SD (Dove Medical Press, 2024)
Bong-Jo Kim,1 Seon-Been Bak,1 Su-Jin Bae,1,2 Hyo-Jung Jin,3 Sang Mi Park,3 Ye-Rim Kim,3 Dae-Hwa Jung,3 Chang-Hyun Song,3 Young-Woo Kim,1 Sang-Chan Kim,3 Won-Yung Lee,2,4 Sun-Dong Park1 1Department of Korean Medicine, Dongguk University, Gyeongju, 38066, Korea; 2Department of Korean Medicine, Wonkwang University, Iksan, 54538, Korea; 3Medical Research Center, College of Korean Medicine, Daegu Haany University, Gyeongsan, 38610, Korea; 4Research Center of Traditional Korean Medicine, Wonkwang University, Iksan, 54538, KoreaCorrespondence: Won-Yung Lee, Department of Korean Medicine, Wonkwang University, Iksan, 54538, Korea, Email wonyung21@wku.ac.kr Sun-Dong Park, Department of Korean Medicine, Dongguk University, Gyeongju, 38066, Korea, Email sundong@dongguk.ac.krIntroduction: Tacrine, an FDA-approved acetylcholinesterase inhibitor, has shown efficacy in treating Alzheimer's disease, but its clinical use is limited by hepatotoxicity. This study investigates the protective effects of red ginseng against tacrine-induced hepatotoxicity, focusing on oxidative stress.Methods: A network depicting the interaction between compounds and targets was constructed for RG. Effect of RG was determined by MTT and FACS analysis with cells stained by rhodamine 123. Proteins were extracted and subjected to immunoblotting for apoptosis-related proteins.Results: The outcomes of the network analysis revealed a significant association, with 20 out of 82 identified primary RG targets aligning with those involved in oxidative liver damage including notable interactions within the AMPK pathway. in vitro experiments showed that RG, particularly at 1000μg/mL, mitigated tacrine-induced apoptosis and mitochondrial damage, while activating the LKB1-mediated AMPK pathway and Hippo-Yap signaling. In mice, RG also protected the liver injury induced by tacrine, as similar protective effects to silymarin, a well-known drug for liver toxicity protection.Discussion: Our study reveals the potential of RG in mitigating tacrine-induced hepatotoxicity, suggesting the administration of natural products like RG to reduce toxicity in Alzheimer's disease treatment.Keywords: AMPK, liver toxicity, oxidative stress, red ginseng, tacrine